Kebahagiaan ditinjau dari Perilaku Bersedekah: Suatu Kajian Psikologi Islam - Rini Julistia; Safuwan Safuwan (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
This study aims to understand happiness in the review of sadaqah behavior in the analysis of Islamic psychology by taking a sample of the community of the Lhokseumawe City and North Aceh District. Happiness is the focus of humans in life that can be understood by people in various interpretations in accordance with knowledge, understanding, and habits of life. This study was designed with an explorative type by qualitative approach, in which the reality of sadaqah behavior became the focus of happiness felt by individuals. The results showed that knowledge about happiness and sadaqah gave importance to individuals as a virtue in lives. Based on this knowledge the individual understands that the reality of giving is able to provide peace of mind which is felt as happiness in his life. Therefore sadaqah behavior continues to be carried out by people in their lives to provide a sense of happiness and enjoyment of life. In accordance with the findings of this study, it was concluded that one source of happiness in the reality of the community of Lhokseumawe city and North Aceh district was to giving of sadaqah accompanied by sincere intentions.